2022
DOI: 10.1186/s12879-022-07855-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molecular diagnostic tests on diagnostic and treatment delays in tuberculosis: a systematic review and meta-analysis

Abstract: Background Countries with high TB burden have expanded access to molecular diagnostic tests. However, their impact on reducing delays in TB diagnosis and treatment has not been assessed. Our primary aim was to summarize the quantitative evidence on the impact of nucleic acid amplification tests (NAAT) on diagnostic and treatment delays compared to that of the standard of care for drug-sensitive and drug-resistant tuberculosis (DS-TB and DR-TB). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Compared to conventional methods for pathogen detection, GeneXpert offers the advantages of rapid detection speed and high accuracy (positive results can be detected when the number of M.tb is >130/mL) ( 41 ). According to a report, the use of GeneXpert reduced diagnostic delay by 1.79 days (95% CI: 0.27–3.85) and treatment initiation delay by 2.55 days (95% CI: 0.54–4.56) compared to sputum microscopy ( 42 ). Currently, GeneXpert technology is only available in certain designated tuberculosis hospitals in China.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional methods for pathogen detection, GeneXpert offers the advantages of rapid detection speed and high accuracy (positive results can be detected when the number of M.tb is >130/mL) ( 41 ). According to a report, the use of GeneXpert reduced diagnostic delay by 1.79 days (95% CI: 0.27–3.85) and treatment initiation delay by 2.55 days (95% CI: 0.54–4.56) compared to sputum microscopy ( 42 ). Currently, GeneXpert technology is only available in certain designated tuberculosis hospitals in China.…”
Section: Discussionmentioning
confidence: 99%
“…Such spatial heterogeneity is common in many countries regardless of income level, and multiple studies have shown that living in a rural area is associated with longer health-seeking delays. ( 4 , 12 , 16 ) Increasing access to health care through initiatives that deliver more patient-centred services (e.g. use of mobile teams in rural areas, adopting clinic opening hours that match patients’ preferences) has proven to reduce delays in health seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid point of care and self-administered testing kits for HIV which can deliver a result within minutes have reduced costs in testing and improved linkage to HIV care [ 9 , 10 ]. Similarly for TB, the widespread implementation of rapid molecular testing which is recommended by the World Health Organization, has led to reduced delays in diagnosis and treatment initiation [ 11 ]. There is an opportunity to build on these achievements to develop rapid diagnostic tests for other pathogens with pandemic and outbreak potential–indeed, to support COVID-19 diagnostic testing, countries employed existing HIV and TB molecular testing platforms.…”
Section: Areas Of Growth and Opportunitymentioning
confidence: 99%